The doctrine of creation : essays in dogmatics, history and philosophy - Gunton, Colin E. (Academic Paperback Ser., 2004)
This study by leading scholars from around the world engages with central hermeneutical, philosophical and theological dimensions of the doctrine of creation. Particular prominence is given to discussion of creation 'out of nothing'm the relation of eternal creator to temporal creation, the Trinitarian construction of the doctrine and its ethical implications. The essays comprise: -Robert Jenson on the doctrine of creation -Paul Helm on eternal creation -Colin Gunton on Genesis and on the Reformers -Alan Torrance on spatio-temporal dimensions -Daniel Hardy on creation and eschatology -Brian Ho.